Bekir Sıdkı Sezgin’in hayatı, sanatı ve besteleri - Çoban, Şemsettin (My University, 2012)
BEKİR SIDKI SEZGİN’İN HAYATI, SANATI VE BESTELERİ Klasik Türk Mûsikî’sinde icrâ ve tavrın önemi büyüktür. XX. yy.’da Türk Mûsikîsi’nin yetiştirdiği en büyük sanatkârlardan biri de Hafız Bekir Sıdkı Sezgin’dir. O, icrâsı, tavrı ve sanat ahlâkı ile Klasik Türk Mûsikîsi’nde ekol haline gelmiş bir okuyucudur. Bununla birlikte sanatkârın hafızlığı ve dînî eğitim almış olmasıyla beslenen güçlü dînî mûsikî icrâsının lâ dînî mûsikî tavrının gölgesinde kaldığı görülmektedir. Bekir Sıdkı Sezgin’in hayatını, sanatını ve bestelerini içini alan çalışmamız giriş ve dört bölümden oluşmaktadır. Bu çalışma, sanatkârı bütüncül bir yaklaşımla en doğru şekilde anlamayı ve ilgililere sunmanın yanında; ilkeli, asil ve manevi aşkınlıkla dolu sanat hayatındaki güzelliklere kapı aralamayı amaçlamaktadır. İcrasındaki titizliği kadar sanatkâr duruşundan ödün vermemesi de mûsikîmize bıraktığı örnek bir mirastır. Sanatçının sahip olduğu doksandan fazla bestesi mûsikî alanındaki maharetini ortaya koymuş olmasına rağmen günümüzde besteleri ve bestekârlığı hak ettiği yeri bulmuş değildir. Bekir Sıdkı Sezgin, Klasik Türk Mûsikîsi, Dînî Mûsikî, İcrâ, Tavır, Bestekârlık.

BEKİR SIDKI SEZGİN’S LİFE, ART AND COMPOSITIONS The importance of performing and style is great in Turkish Classical Music. One of the most important musicians that Turkish Music had trained up in the twentieth century is Hafiz Bekir Sıdkı Sezgin. He is a singer that has become an ekol with his performing and his art ethics in our music. However, it has been seen that his religious music - fed with religious education and memorising Quran- has remained in the shade of his secular music performing. Our study includes Bekir Sıdkı Sezgin’s life, art and compositions and consist of an introduction and four chapters.This study has intended to understand the musician completely in the most accurately form, present to the relevants and open a door to the beatuies in his art life that is principled, noble and full of spritüal trascendence.His non-compromising in his art is an important example style as his particularly in his performing which he has bequathed in our music .Although his compositions more than 90 have demonstrated his ability in the music area, his art and composerness haven’t taken up a position in where they should have been in our time. KEY WORDS: Bekir Sıdkı Sezgin, Turkish Classical Music, Religious Music, Performing, Style, Composerness.
Keywords: Besteciler_Türk Müziği